The Measure of Residential Segregation of Socio-Economic Groups by Using Multigroup Indices in Shiraz City - Mohammad Hassan yazdani; Ali Soltani; Hossein Nazmfar; Mohammad Amin Attar (تحقیقات کاربردی علوم جغرافیایی)
Urban segregation has been a problem of many cities of the world. Many researchers have interested in the urban segregation issues. Urban segregation has strongly concentrated poverty and created underclass. Different types of urban segregation exist, including income and racial or ethnical segregation, and depending on the contextual mechanisms within a city. To understand and plan a better community, urban planners needs to know how to measure the segregation and interpret the results. There have been many developments of segregation measures. Some evolved and some remained unchanged. This paper is studied the most used multigroup measures of residential segregation (8 indicators) in Shiraz city and between different socio-economic groups of it by using of the Segregation Analyzer Software. In general, the results show the occurrence of segregation in the medium amount to the high amount and by the calculated values of 0/7177, 0/5785, 0/5474 – 1, 0/5407, 0/3969, 0/3759, 0/3613, 0/3375 in the city of Shiraz. On the other hand, the use of Hot spots Analysis in the study area shows that the greatest concentrations of the socio-economic high group are in almost near the center of Shiraz city and the northwest of city, and for the socio-economic medium group exists in the west of city. Also there is the greatest concentration of the socio-economic low group in the southwest of Shiraz city.